Systematic histology and evidence for the male reproductive activity of Amphibalanus amphitrite (Darwin, 1854) - Senarat, Sinlapachai; Kaewnuan, Romfa; Sudtongkong, Chanyut; Boonyoung, Piyakorn; Sukparangsi, Woranop; Kongtueng, Piyamat; Srivorakul, Saralee; Wongkhamhaeng, Koraon; Charoenphon, Natthawut; lida, Atsuo; Kenthao, Anan (Invertebrate Biology, 2024)
The striped acorn barnacle, Amphibalanus amphitrite, a taxon of Balanidae, is commonly found along Thailand's coastline. In this study, we used histological methods to describe the microscopic anatomy of A. amphitrite. All samples (n = 30) were obtained from the seagrass beds of Libong Island, Thailand, in the Andaman Sea. Histological observation of various longitudinal sections from specimens of A. amphitrite provides clear insights into the organization of organ systems in the species. The digestive tract was observed to be mainly divided into four subregions, including the cuticle‐lined mouth and esophagus, which is characterized by a high columnar epithelium, the stomach, and the intestine. The accessory organ, including the digestive gland, exhibited lobulated structures and was covered with low columnar epithelial cells on a thin layer of smooth muscle. Furthermore, we examined the reproductive system, including both the ovary and testes, as well as the process of gametogenesis. Testicular development was predominantly observed during active breeding seasons throughout the observation.